Pengaruh Leverage, Intensitas Aset Tetap, Transfer Pricing, Dan Komite Audit Terhadap Manajemen Pajak Dengan Indikator Tarif Pajak Efektif - Firmansyah (Jurnal Literasi Akuntansi, 2022)
Purpose: This study aims to examine the effect of Leverage, fixed asset intensity, transfer pricing, and audit committee on tax management in manufacturing companies listed in the IDX for the 2018-2021 period. Method: Sampling used purposive sampling method and produced 102 samples data. Data analysis techniques with multiple linear analysis. Finding: The results obtained indicate that Leverage, transfer pricing and audit committee have no effect on tax management. While the variable intensity of fixed assets has a positive influence on tax management. Novelty: This study considers the addition of transfer pricing and audit committees because they are rarely studied in Indonesia.